Nobility in the captaincy of goiás from the perspective of oversea dominions - Moraes, Cristina de Cássia Pereira (2014)
Current paper analyzes nobility in the modern period from the perspective of the overseas dominions. A short introduction on the landed nobility in the Captaincy of Goiás in the eighteenth century is forwarded as an example of our research. The paper is divided into two parts: the first part deals with the concept of nobility during the medieval period and simultaneously the transformations which occurred within the nobility in modern times; the second part shows the nobility of the Captaincy of Goiás from the perspective of overseas dominions. In other words, the possibility of creating a group of typical noble people overseas and the dynamics which resulted from the colonization process are discussed. Therefore, the article investigates the statute of the Portuguese nobility and its repercussions in mining areas which disrupted the stigma of people born outside Portugal and established privileges for services rendered in the hinterland of State Goiás. The above foregrounded a new social basis in the late 18th century and in the beginning of the 19th century.